IDENTIFICATION OF BLACK SPOTS ON STATE HIGHWAY-75 - Miss. Mayuri A Shirgurkar; Prof. Dhananjay S Patil (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The issue of road accidents is an increasing problem in developing countries. There are many steps required to achieve road safety measures. Road safety is necessary to reduce accident involving both human and vehicle damage. The safety deficiencies were detected to minimize accidents and to save road users. By studying the various accident parameters and by using accident rate method, accident black spots analysis is done. The data is analysed by developing regression model. Using such analysis blackspots locations were identified for further improvement in road safety and also the causes of accident are studied. For the study Sangli – Kolhapur road (SH-75) is taken having longitude and latitude for sangli (N 16.8530, E 74.5630) and for Kolhapur (N16.7290, E 74.2824).